Local Wisdom Fly Trap Effectiveness in the Culinary Area of Bantul Beach Tourism, Yogyakarta - Asep Rustiawan; Muchamad Rifai (Epidemiology and Society Health Review (ESHR), 2022)
Background: Flies are insects that can contaminate food with various harmful disease agents. It is not yet known which fly trap is the most effective at trapping flies. There are three types of fly traps as local wisdom for the culinary area of Bantul Beach, which is used to control fly populations: sticky paper, plastic bowls, and plastic bottles. This study aims to determine the effectiveness of sticky paper, plastic bowls, and plastic bottles in trapping flies. Method: This research was an experimental study with three fly traps: sticky paper, plastic bowls, and plastic bottles. Measurements were made by placing fly traps in 12 seafood stalls in the culinary area of Bantul Beach. The number of trapped flies was counted by hand counter. Data were analyzed using the One-Way ANOVA test, significance level (α) = 0.05, and Post Hoc Test Multiple Comparison advanced test. Results: Sticky paper could trap 297 flies (69.4%), followed by 121 plastic bowls (28.3%) and ten plastic bottles (2.3%). The analysis showed that sticky paper had significantly different effectiveness in trapping flies compared to plastic bowls (p = 0.032) and plastic bottles (p = 0.004). In contrast, the efficacy of plastic bowls and bottles was not significantly different (p = 0.130). Conclusion: The effectiveness of sticky paper in trapping flies was significantly different from that of plastic bowls and plastic bottles, while the efficacy of plastic bowls and plastic bottles was not significantly different.